О древней мечети в Эски-Сарае (письменные свидетельства) - Королева, Л.И. (Культура народов Причерноморья, 2013)
В позднее средневековье, очевидно, поселение в Эски-Сарае было относительно многолюдным и основным населением здесь были татары. Существует версия, что это поселение было основано ранее, чем средневековый город Ак-Мечеть и являлось его предшественником, но когда именно оно было основано, сказать определенно нельзя, предположительно расцвет Эски-Сарая можно отнести к концу 15 – самому началу 16 века. Мы определяем более позднюю датировку мечети, а именно: 16-18 вв. А если верить рассказу Эвлия Челеби, эта дата сдвигается к периоду от 1666 г., не ранее. Мечеть, судя по ее размерам и наличию дополнительного михраба снаружи, была соборной, малая мечеть служила для посещений высокопоставленного сановника (очевидно калги-султана). Мечеть в Эски-Сарае по ряду особенностей является уникальной и к тому же одной из немногих, среди уцелевших памятников периода Крымского ханства в Симферопольском районе. По поводу развалин неизвестного происхождения, существует две версии: либо это остатки монетного двора, либо старый дворец калги-султана. У пізнє середньовіччя, очевидно, поселення в Ескі-Сарай було відносно багатолюдним і основним населенням тут були татари. Існує версія, що це поселення було засноване раніше, ніж середньовічне місто Ак-Мечеть і було його попередником, але коли саме воно було засноване, сказати точно не можна, імовірно розквіт Ескі-Сарай можна віднести до кінця 15 - початку 16 століття. Ми визначаємо більш пізню дату мечеті, а саме: 16-18 ст. А якщо вірити розповіді Евлія Челебі, ця дата зсувається до періоду від 1666 р., не раніше. Мечеть, судячи з її розмірами і наявності додаткового міхрабу зовні, була соборною, мала мечеть служила для відвідувань високопоставленого сановника (очевидно калги-султана). Мечеть в Ескі-Сарай по ряду особливостей є унікальною і до того ж однією з небагатьох, серед уцілілих пам'яток періоду Кримського ханства в Сімферопольському районі. З приводу руїн невідомого походження, існує дві версії: або це залишки монетного двору, або старий палац калги-султана. The Main object of this research is the Eski mosque in-Shed, unique and unique monument of the Crimean Tatar architecture of the period of the Crimean khanate. Eski-Saray (in Tatar means «old Palace») - Tatar village of Taurian province Simferopol district, modern C. Pioneer, located in the valley of R. Salgir in 14 km from Simferopol. In the complex of the mosque we consider the ruins of an unknown destination, nearby. Undoubtedly of great interest for us is the settlement of Eski-Saray, the history of which logically should be linked with the history of medieval AK-mosque. For holistic studies ancient monuments of history and architecture is necessary to unite efforts of such fields of knowledge as architecture, archaeology, and they, in turn, become strong in their constructions, when are based on data extracted from the written sources. Word to the architectural appearance of the mosque has already been expressed in the book E.V. Heckler «Monuments of the Crimean Tatar architecture» in 1998. This study has attempted to collect all currently available written evidence, Dating mainly from the second half of the 17th century to our time, of the antiquities and settlement in Eski-Shed and analyze them, except that in the second part of the study highlights the question of the history of protection of the Eski mosque-a Barn. We define later Dating mosque, namely: 16-18 centuries, And if you believe the story Evliya Celebi, this date is shifted to the period from 1666, not earlier. Mosque, judging by its size and presence of additional mihrab outside, was the Cathedral, a small mosque was used for visits of the high-ranking dignitary (obviously kalgi- Sultan). Mosque in Eski-Barn on a number of features is unique and one of the few among the surviving monuments of the period of the Crimean khanate in Simferopol district. Over the ruins of unknown origin, there are two versions: either it is the remains of the mint, or the old Palace kalgi-Sultan.